(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The article presents the results of a survey, the aim of which was to attempt to assess the knowledge of issues related to local self-government budget by the X generation representatives and to check the level of their activity in creating the budget of local government units. The first part of the article presents the analysis of the assessment of the respondents’ level of knowledge on the functioning of local self-government units and their budget. It also indicates the sources respondents obtain information from on the budget functioning of local self-government units. In the following parts of the article, the level of activity of the X generation representatives is evaluated in terms of budgeting of local self-government units. The analysis of obtained results allows to conclude that despite X generation representatives declaring low level of interest in local self-government units’ activity, they still consider their own knowledge in this field as relatively high. Although actively not involved in creating budgets of their local government units, most of the survey’s respondents want to have the right to participate directly in the process.